The contribution of new businesses to regional employment: an empirical analysis of the direct employment effect - Michael Fritsch; Yvonne Schindele (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We investigate regional differences in the contribution of newly founded businesses to regional employment. This is labeled the direct employment effect of new businesses. The analysis is at the spatial level of West German planning regions for the period 1984-2002. We find rather pronounced differences for the direct employment effect across regions. Regression analyses for explaining these differences show that the start-up rate, the education level of the regional workforce, and an entrepreneurial character of the regional technological regime have a positive impact on the direct employment effect of new businesses. The overall effect of population density is negative, but the marginal effect is positive for regions beyond a certain threshold. Our results suggest that the success of the new businesses is not at the expense of the incumbents but that direct and indirect employment effects of new businesses are positively interlinked.
Keywords: L26; M13; O1; O18; R11; 330; Entrepreneurship; new business formation; regional development; direct employment effect; Unternehmensgründung; Unternehmensentwicklung; Beschäftigungseffekt; Regionale Entwicklung; Deutschland